A hierarchical facility layout planning approach for large and complex hospitals - Stefan Helber; Daniel Böhme; Farid Oucherif; Svenja Lagershausen; Steffen Kasper (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2014)
The transportation processes for patients, personnel, and material in large and complex maximum-care hospitals with many departments can consume significant resources and thus induce substantial logistics costs. These costs are largely determined by the allocation of the different departments and wards in possibly multiple connected hospital buildings. We develop a hierarchical layout planning approach based on an analysis of organizational and operational data from the Hannover Medical School, a large and complex university hospital in Hannover, Germany. The purpose of this approach is to propose locations for departments and wards for a given system of buildings such that the consumption of resources due to those transportation processes is minimized. We apply the approach to this real-world organizational and operational dataset as well as to a fictitious hospital building and analyze the algorithmic behavior and resulting layout.
Keywords: 330; Hospital layout planning; quadratic assignment problem; fix-and-optimize heuristic